Oecologia - Oecologia (Springer Nature, 2026)
Oecologia is an international journal dedicated to publishing innovative ecological research of broad interest. Cited more than 29,000 times in 2024, making it a highly referenced source in ecology. Welcomes research across the entire field of ecology, supporting and advancing the UN's sustainable development goals. Welcomed topics include physiological ecology, conservation ecology, behavioral ecology, population and community ecology, plant-microbe-animal interactions, ecosystem ecology, global change ecology, and conservation ecology. Dedicated section of Highlighted Student Research. Each year, two awards are given to the outstanding papers by student authors. Charges no publication fees unless opting for open access. Led by a renowned team of Editors-in-Chief and a distinguished Editorial Board.
FI 0.73
Q2
Keywords: Life Sciences; Ecology & Organismal Biology; Ecología; Biología de los organismos; Acuerdos transformativos; Transformative agreements; Ecología fisiológica